Antropologi Minang Dalam Perspektif Al-Qur’an: Kajian Sistem Keturunan Materilinial - Muhammad Taufiq (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2022)
This research is about matrilineal in the Minangkabau community from the perspective of the Qur'an. This research was made in order to answer the impression of differences in normative values in the Minangkabau custom with the reality found in the Minang community. In the debates of scientists there are those who agree or reject and some even agree with the record of matrilineal norms if they are associated with the Qur'an. The purpose is to find out how the Qur'an views the concept of Matri. The object of this study, anthropological value in the matrilineal concept adopted by the Minang tribe when viewed from the Qur'an. This research is a library reseach or library research. Data sources consist of primary sources such as the tafsir al-Maraghi, Ibn Katsir, Tafsir alMuyassar and Tafsir Hamka. Meanwhile, secondary data from books and journals as well as blogs about Anthropology and Minang culture are related to this research. The conclusion in this study is that the concept of matriarchate in the Minang tribe is not contrary to the universal values brought by the Qur'an and the concept of the Basandi Syarak custom, syarak basandi kitabullah is embodied in Minang society and is in line with the Qur'an.